Macleod's clinical examination - Macleod,John; Douglas,Graham; Nicol, E. Fiona; Robertson,Colin (Edinburgh: Elsevier Churchill Livingstone, 2005)
Describes the practical skills every clinician must acquire and develop in order to evolve diagnostic procedures and management strategies and plans. Its main purpose is to document and explain how to: talk with a patient; take the history from the patient; examine a patient; formulate your findings into differential diagnoses and rank these in order of probability; and use investigations to support or refute
Section 1 History taking and general examination History taking General examination Section 2 Systemic examination The cardiovascular system The respiratory system The gastrointestinal system The renal system The reproductive system The nervous system including the eye Examination of the ear, nose and throat The musculoskeletal system Section 3 Special situations Babies and children The critically ill patient
Includes index.
Keywords: Physical diagnosis; Medical history taking; Physical Examination